2022
DOI: 10.1007/s00784-021-04362-0
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation of gingival lesions resulting from autoimmune diseases: systematic review and meta-analysis

Abstract: Objectives To evaluate the effects of photobiomodulation (PBM) in gingival lesions resulting from autoimmune diseases; to compare PBM and topical corticosteroid (CS) treatment; and to assess PBM outcome over time of follow-up. Materials and methods A comprehensive electronic search was performed in four electronic databases. Treatment effects were measured through visual analog scale of pain (VAS) and clinical evolution of lesion (Thongprasom scale for oral lichen planu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The studies included in this systematic review showed that the biological effects of PBM treatment are beneficial compared to those of other conventional therapies such as corticosteroids [ 26 , 30 , 32 ] as shown by the reduction of symptoms such as pain and signs associated with LPO lesions, highlighted by de Carvalho et al [ 24 ]. Other authors clarified that, in addition to PBM, there is another type of therapy, i.e., high-power laser (HLLT) [ 33 ] which, they claim, allow achieving significantly better results than PBM in the aforementioned parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies included in this systematic review showed that the biological effects of PBM treatment are beneficial compared to those of other conventional therapies such as corticosteroids [ 26 , 30 , 32 ] as shown by the reduction of symptoms such as pain and signs associated with LPO lesions, highlighted by de Carvalho et al [ 24 ]. Other authors clarified that, in addition to PBM, there is another type of therapy, i.e., high-power laser (HLLT) [ 33 ] which, they claim, allow achieving significantly better results than PBM in the aforementioned parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should always be kept in mind that PBM therapy is not applied to cure lesions but rather to improve the aforementioned clinical aspects, as reported in the studies by Mutafchieva et al [ 30 ] and Khater et al [ 32 ], who described that most of their patients obtained a moderate recovery, and some a complete one. These poor results are due to the lack of a long-term follow-up after therapy administration, as pointed out by Hanna et al [ 21 ] and Carvalho et al [ 24 ], which also makes it difficult to assess the possible side effects that PBM can produce in the long term, although we already know that it is much less invasive than other conventional treatments such as corticosteroids. In addition, it was observed in different studies such as Mirza et al [ 29 ], Lavaee et al [ 31 ] and Ferri et al [ 38 ] that, in the short term, no side effect was been detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis that analyzed 17 studies has concluded that photobiomodulation determined an overall amelioration of clinical scores and significant pain reduction of treated areas, similar to topical corticosteroids, thus representing a viable alternative [ 95 ]. Although the preliminary results are promising, these alternative therapies should be further tested and compared to the classical therapy in order to assess their efficacy over time and for different disease stages.…”
Section: Management Of the Patient With Dg In The Dental Office And N...mentioning
confidence: 99%